1999
DOI: 10.1017/s0003598x00087809
|View full text |Cite
|
Sign up to set email alerts
|

Gibraltar Neanderthals and results of recent excavations in Gorham's, Vanguard and Ibex Caves

Abstract: In December 1998, we presented a Special section on great finds and publications of 1848. The discovery of the Gibraltar skull was in that famous year. Now, 150 years later new excavations and a recent conference have once again focused interest on this, the first place where Neanderthal remains were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 8 publications
1
41
0
2
Order By: Relevance
“…), strawberry tree fruit (Arbutus unedo) and pine nuts (Pinus spp.). Furthermore, other studies have also indicated that plants were important parts of Neanderthal diets not only in southernmost parts such as at Gorham's Cave in Gibraltar (Barton et al, 1999), but even in northern parts of Spain (Hardy et al, 2012). Therefore, plant foods may have been especially important in Neanderthal diets in southeastern Iberian refugia.…”
Section: Evidence Of Neanderthal Plant Consumptionmentioning
confidence: 97%
“…), strawberry tree fruit (Arbutus unedo) and pine nuts (Pinus spp.). Furthermore, other studies have also indicated that plants were important parts of Neanderthal diets not only in southernmost parts such as at Gorham's Cave in Gibraltar (Barton et al, 1999), but even in northern parts of Spain (Hardy et al, 2012). Therefore, plant foods may have been especially important in Neanderthal diets in southeastern Iberian refugia.…”
Section: Evidence Of Neanderthal Plant Consumptionmentioning
confidence: 97%
“…Nuts and other large seeds, though energyrich, long lasting, and locally common in temperate forests, are relatively expensive to process, and snow cover greatly raises the winter search costs of these resources. Seed and nut hull fragments are occasionally found in Lower and Middle Paleolithic sites (e.g., Barton et al, 1999), but there are no archaeological indications of stockpiled plant foods or the grinding equipment necessary to increase their digestibility. Meat was likely to have been the critical food source in winter, even if a wider variety of foods were consumed in other seasons of the year.…”
Section: Paleolithic Backgroundmentioning
confidence: 99%
“…on the Iberian Peninsula (36). Dates on levels containing Mousterian cultural remains, but no human fossil remains at Zafarraya, Spain (36), Caldeirão, Figueira Brava, and Foz de Enxarrique in Portugal (37), and Gorhams Cave in Gibraltar (38) suggest that Neandertals may have existed in the latter region until Ϸ30 ka B.P. In addition, level G 1 at Vindija Cave in northern Croatia yielded fragmentary, but clearly Neandertal, human remains that were dated to this same time span (see below).…”
Section: Chronology and Perspectives On Neandertal Phylogenymentioning
confidence: 99%